Hambatan dalam Adopsi Layanan Online Perbankan pada Mahasiswa Akuntansi: Structural Equation Modeling - Arya Dika Ferdiansyah; Budi Barata Kusuma Utami (Value: Jurnal Manajemen dan Akuntansi, 2025)
In the era of modern technological development, banking companies in Indonesia innovated by creating mobile banking technology to facilitate financial transaction services. In contrast, Although mobile banking provides convenience for its users, there are still many barriers for customers to use mobile banking. This study aims to identify barriers to the adoption of mobile banking technology. This research uses quantitative methods. The sample in this study were 101 Indonesian accounting students. The data analysis technique in this study used Structural Equation Modeling (SEM). The results of this study indicate that the image barrier and value barrier affect the barrier to the usage of mobile banking. while the risk barrier and tradition barrier have no effect on the barrier to the usage of mobile banking.